2002
DOI: 10.1046/j.1365-2133.2002.04584.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal barrier lipids in human vernix caseosa: corresponding ceramide pattern in vernix and fetal skin

Abstract: The composition pattern of ceramides mirrors that of mid-gestational fetal epidermis. Vernix thus represents a 'homologous' substitute for the immature epidermal barrier in fetal skin. The differential role of individual ceramides in this process remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 43 publications
5
78
0
5
Order By: Relevance
“…10 On the other hand, infants aged 6-24 months showed significantly lower levels of ceramide than children of other ages. 25 A limitation of our study was the lack of clarifying the differences in SC characteristics of infants from those of adults specifically in terms of by two major factors: NMF and ceramide. Minami-Hori et al reported that SC functions are not determined by single factors such as NMF, ceramides, etc., but are the result of the overall effects of numerous SC components that vary during growth.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the other hand, infants aged 6-24 months showed significantly lower levels of ceramide than children of other ages. 25 A limitation of our study was the lack of clarifying the differences in SC characteristics of infants from those of adults specifically in terms of by two major factors: NMF and ceramide. Minami-Hori et al reported that SC functions are not determined by single factors such as NMF, ceramides, etc., but are the result of the overall effects of numerous SC components that vary during growth.…”
Section: Discussionmentioning
confidence: 99%
“…Их действие усиливает образование собственных липидов, уменьшает признаки раздражения, восстанавлива-ет кожный барьер и ограждает от действия раздражающих факторов внешней среды. Повышение синтеза собственных липидов -важный положительный эффект, т. к. многие кремы и мази содержат различные церамиды и лишь ими-тируют естественный состав липидов кожи [18,19].…”
Section: нарушение защитной функции кожиunclassified
“…In contrast, FFA represent the dominant lipid in both post-and pre-natal skin [32]. It is estimated that ~30% of the lipids of the vernix caseosa originate from the epidermis with the remainder coming from sebaceous glands.…”
Section: The Development Of Skin Barrier Functionmentioning
confidence: 99%
“…The periderm acts as the interface between the amniotic fluid with the developing epidermis prior to SC formation; later the periderm sheds to become part of the vernix caseosa at 15-20 wk GA. The effects of GA and PNA on the histological development of the epidermis were reported in 169 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) infants aged from a few hours to 1 year old [11]. The thickness and number of epidermal cell layers, the degree of undulation of the dermo-epidermal junction, and the SC thickness increased clearly with GA in children who had died within 7 days of birth; both the SC and the dermo-epidermal undulations were barely perceptible until 34 wk GA.…”
Section: The Development Of Skin Barrier Functionmentioning
confidence: 99%